IMPROVING THE RELATIONSHIP OF THE COACH-ATHLETE DIODE IN SPORTS SCHOOLS (American Journal of Business Management, Economics and Banking, 2024)
The coach-athlete relationship is a crucial aspect of sports education, particularly in sports schools where young athletes develop both their skills and character. This article explores strategies to improve and strengthen this relationship, emphasizing its significance in fostering athletes' holistic development and achieving sporting success.